Innovation in halal packaging and labeling to enhance Indonesian processed food export performance - Alya Viyan Nada; Hendri Hermawan Adinugraha (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
This study examines the role of packaging innovation and halal labeling in increasing the selling value of Indonesian traditional processed food products for export markets in the Middle East. As the country with the largest Muslim population in the world, Indonesia has significant potential to strengthen its position in the global halal industry, particularly in the food sector. This article aims to analyze how packaging innovation through modern, functional, and culturally appropriate designs, along with the presence of a trusted halal label, can increase product competitiveness in the international market. The method used is descriptive qualitative, with a literature study approach and analysis of previous research results. The results show that packaging innovation not only functions to protect and preserve products but also serves as a communication medium that conveys product identity and quality. Furthermore, the halal label serves as a symbol of trust that guarantees compliance with sharia principles and international standards, thereby increasing consumer confidence. The synergy between innovative packaging and a trusted halal label creates a significant competitive advantage, enabling Indonesian traditional food products to penetrate the premium halal market segment in the Middle East. This study concludes that effective collaboration between producers, the government, and certification bodies is crucial to optimizing the export potential of the Indonesian halal industry.